Source of lunette dune sediments: a geomorphic terrain analysis approach in Etosha National Park, Namibia - Hipondoka, Martin H. T.; Busche, Detlef; Kempf, Jürgen (ERDKUNDE, 2004)
The presence of so-called lunette dunes in the lee of pans in northern Namibia sprouted a discussion on the formation of the shallow basins related to them. These lunette dunes are made up of larger particles than those found in the pans, from which the sediments are thought to have originated. At Etosha Pan, this contradiction is compounded by the fact that the dunes are found on the northwestern and western side of the pan, whilst the prevailing dominant wind, believed to have played a formative role in their development, blows from the northeast. Ancillary data, in concert with high-resolution, multi-date satellite imagery were examined through the prism of geomorphic terrain analysis. The resultant indicators unequivocally point to the Ekuma delta, on the northwestern rim of the pan, in direct opposition to the pan floor proper, as the source of these dune sediments. It is therefore probable that coarser sediments found on the lee side of similar pans can be similarly explained as originating from former inlet deposition and not from wind excavation in the process of pan initiation as popularly held.